Review on a palm vein infrared image acquisition system - Mohd Noh, Zarina; Ramli, Abdul Rahman; Hanafi, Marsyita; Saripan, M. Iqbal (IEEE, 2013)
Palm vein recognition system is one of the modalities in biometric technology. It manipulates the vast pattern of vein under the palm as one of the measurements in validating a person with his or her claimed identity. One of the components in a palm vein recognition system is the image acquisition part. With a suitable configuration, the image acquisition system may capture the required image, just enough for the recognition process. This paper is a brief review on the development needs of a palm vein image acquisition system.